Problem-Based Learning Strategy Development in Vocational High School Field of Expertise Technology and Engineering in DKI Jakarta Province - Arum Setyowati; Rusmono Rusmono (Peneliti.net, 2022)
The research aims to develop a PBL strategy for SMK in the field of technology and engineering expertise, by producing learning materials for applying electronic circuits with a PBL strategy. Using research and development methods, with the Dick and Carey model which consists of the design, development, and evaluation stages. At the design and development stage, materials for the application of Electronic Circuits with a PBL strategy are produced. At the evaluation stage, it is divided into 3 (three) stages, one on one evaluation by experts and by students; small group evaluation; and field trials. The results of the study materials for the Application of Electronic Circuits with the PBL strategy by instructional design experts and materials experts obtained an average of 87.12% and 88.44% with very decent predicates. The results of the one-to-one evaluation by students obtained 89.74%. Small group evaluation results obtained 94.28% of students can understand the characteristics of easy learning. The results of the field trial obtained 92.61%. Conclusion of learning materials for the Application of Electronic Circuits with a PBL strategy that is feasible to use.